2019
DOI: 10.1177/0883911519881715
|View full text |Cite
|
Sign up to set email alerts
|

Heat-curing polylactide for bone implants: Preparation and investigation on properties relevant to degradation

Abstract: Several processes have been used to produce polylactide for bone replacement. The challenge remains, however, to produce these devices by a simpler and more economical process. In this study, a method of combining powder and liquid parts was introduced. Star-shaped polylactides with molecular weights ranging from 3 to 16 kg/mol were synthesized and blended with a linear polylactide (Mw = 188 kg/mol) using the technique of emulsion solvent evaporation. The blends in a form of spherical powder were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Powder Part: The star-shaped PLA (MW = 10,770 g/mol, L-form) was blended with the linear PLA (MW = 188,030 g/mol) at a weight ratio of 8/2. The blended PLA powder was prepared by emulsion technique to achieve a spherical powder [5]. Benzoyl peroxide (BPO), an initiator, was added in the powder part in various amounts as indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder Part: The star-shaped PLA (MW = 10,770 g/mol, L-form) was blended with the linear PLA (MW = 188,030 g/mol) at a weight ratio of 8/2. The blended PLA powder was prepared by emulsion technique to achieve a spherical powder [5]. Benzoyl peroxide (BPO), an initiator, was added in the powder part in various amounts as indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Its mechanical stability and bioactivity may enable a prospective application for bone implants. The 4-arm PLA was used in developing the heat-curing PLA [5]. Powder of the 4-arm and linear PLA blend was hardened by heat when mixed with the liquid of dimethacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Dusunceli studied tensile relaxation on PLA and PLA/hydroxyapatite (HA) and found that both strain rate and temperature had great effects on the mechanical responses of the materials 26 . Our previous studies employed a three‐point bending test to investigate the flexural strength of PLA and PLA/HA under different degradation conditions 27,28 . Each mechanical testing method has its own benefits for certain applications.…”
Section: Introductionmentioning
confidence: 99%